The Importance of Publicity and e-WOM in Strengthening Tourist Intentions to Visit Mount Merapi National Park - Suhud, Usep; Allan, Mamoon; Setiawati, Rahmi; Adirestuty, Fitranty; Nurfitriana, Annis; Fitrianna, Hafizh; Hoo, Wong Chee (Journal of Ecohumanism, 2025)
Studies of tourist behaviour in the national parks’ context are still scant. Thus, this study examines the effect of publicity, e-WOM, destination image, and destination preference on tourists' intentions to visit Merapi National Park. Data collected in Greater Jakarta involved 233 participants. Data were analysed using exploratory factor analysis and structural equation models. As a result, publicity and e-WOM significantly affect destination preference and destination image. In addition, destination image crucially influences destination preference, and destination preference significantly affects visit intention. These findings broaden the study of national tourism parks and volcano tourism.